2011
DOI: 10.1590/s1517-83822011000400042
|View full text |Cite
|
Sign up to set email alerts
|

The inhibitory effect of calcium on Cylindrospermopsis raciborskii (cyanobacteria) metabolism

Abstract: Cylindrospermopsis raciborskii (Woloszynska) Seenaya & Subba Raju is a freshwater cyanobacterium of worldwide distribution. In the North-eastern region of Brazil many eutrophic water reservoirs are characterized by the dominance of C. raciborskii, with recurrent occurrence of blooms. These water bodies have high conductivity due to a high ionic concentration, and are defined as hard (with high values of CaCO 3 ). In this study, we investigated the long-term effect (12 days) of high calcium concentration (8 mM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2013
2013
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 16 publications
1
4
0
1
Order By: Relevance
“…1, Table 2). The results were corroborated by data from Carneiro et al (2011), who showed that growth in Cylindrospermopsis was inhibited by a continued exposure to high Ca 2 ' (8 mM). A field survey was implemented by Ye et al (2010), who showed that Ca 2 ' concentration was about 57.73 mg/l in the northern rivers of the Taihu Basin where large Microcystis blooms often occurred.…”
Section: Discussionsupporting
confidence: 68%
“…1, Table 2). The results were corroborated by data from Carneiro et al (2011), who showed that growth in Cylindrospermopsis was inhibited by a continued exposure to high Ca 2 ' (8 mM). A field survey was implemented by Ye et al (2010), who showed that Ca 2 ' concentration was about 57.73 mg/l in the northern rivers of the Taihu Basin where large Microcystis blooms often occurred.…”
Section: Discussionsupporting
confidence: 68%
“…Previously, an inhibitory effect of calcium chloride on C. raciborskii (T3) metabolism was reported [37]. Studying C. raciborskii saxitoxin biosynthesis in vitro , Kellman and Neilan [38] revealed that Ca 2+ was inhibitory.…”
Section: Resultsmentioning
confidence: 99%
“…It also is linked integrally to river flow, and generally increases during periods of low flow because of lack of dilution from water with lower ionic content, a trend also evident in our data set (data not shown). Many of the major ions contributing to conductivity, e.g., Ca 21 , Cl 2 , Na 1 , K 1 , and Mg 21 , influence important metabolic processes or enhance/suppress growth in cyanobacteria (Seale et al 1987, Parker et al 1997, Carneiro et al 2011. Individual ions/compounds that contribute to conductivity may play a role in regulating Phormidium accrual, but further research is required to test this suggestion.…”
Section: Drivers Of % Phormidium Proliferationsmentioning
confidence: 99%